Ocular Manifestations of COVID-19 in a Patient with ANCAAssociated Vasculitis Treated with Rituximab. A Case Report - M. D. Suprun; T. V. Beketova; V. V. Babak; M. D. Evsikova (Oftalʹmologiâ, 2022)
The World Health Organization announced a new coronavirus pandemic on 11 March 2020. It is known that the most frequent clinical manifestation of a new coronavirus infection is lung damage with the evolution of pneumonia, as well as respiratory distress syndrome. The highest risk of severe traction and death is known to occur in the immunosuppressive group of patients. These patients include rheumatologically patients. Currently, there is no complete understanding of the pathogenesis of the development of covid-19, as well as the pathogenesis of the development of autoimmune diseases. In a pandemic, the question of how the coronavirus infection proceeds in patients on immunosuppressive therapy, in particular on anti-B cell, is relevant. In our case report presents a 69-year-old female with ANCA-associated vasculitis remission having received a B-cell-depleting therapy with rituximab (RTX), who had an ocular lesion as a clinical manifestation of Coronavirus disease 2019 (COVID-19). Two months after RTX treatment, COVID-19 was diagnosed. The patient had extrapulmonary manifestations including central nervous system involvement and ocular symptoms such as conjunctivitis, without respiratory pathology. In this clinical observation, the patient’s disease manifested itself with right-sided conjunctivitis, which is a rare manifestation as the first symptom. This article describes the features of the course and outcome of the disease, as well as, the protective effect of RTX in course of COVID-19 is discussed. A comparative analysis of cases of COVID-19 with eye damage is being carried out. This clinical observation is of great value for doctors of all specialties, especially ophthalmologists. A multidisciplinary approach is crucial to manage COVID-19.